Analysis of Inflatable Dams under Hydrostatic Conditions - K. El-Jumaily, Karim; Ali Salih, Abdulah (Journal of Engineering and Sustainable Development, 2005)
Inflatable dams are flexible cylindrical inflatable and deflatable structures made of rubberized material attached to a rigid base and inflatable by air, water, or a combination of air/water. The interest in inflatable dams is increasing because of the ease of placement and construction. Behavior of air or water inflated dams is physically studied and analyzed under different conditions of internal pressure, upstream and downstream heads of water. Experimental data obtained on laboratory test facility for with air and/or waterinflated dams are presented and compared with the theoretical results based on a developed computer program describing dam height, cross sectional profiles and dam cross-sectional area. Good agreement was obtained between theory and experiment results.